Pragmatics as Metacognitive Control - Kissine, Mikhail (Frontiers in Psychology, 2016)
The term “pragmatics” is often used to refer without distinction, on one hand, to the contextual selection of interpretation norms and, on the other hand, to the context-sensitive processes guided by these norms. Pragmatics in the first acception depends on language-independent contextual factors that can, but need not, involve Theory of Mind; in the second acception, pragmatics is a language-specific metacognitive process, which may unfold at an unconscious level without involving any mental state (meta-)representation. Distinguishing between these two kinds of ways context drives the interpretation of communicative stimuli helps dissolve the dispute between proponents of an entirely Gricean pragmatics and those who claim that some pragmatic processes do not depend on mind-reading capacities. According to the model defended in this paper, the typology of pragmatic processes is not entirely determined by a hierarchy of meanings, but by contextually set norms of interpretation.